2012
DOI: 10.1111/j.1476-4431.2012.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative thoracic radiographic findings in dogs presenting for gastric dilatation‐volvulus (2000–2010): 101 cases

Abstract: The most common findings on preoperative thoracic radiographs include esophageal dilation, microcardia, and a small vena cava while the incidence of pulmonary nodules was low. A negative association between survival and presence of cardiomegaly on preoperative thoracic radiographs in dogs with GDV supports the need to obtain these images for prognostic information in spite of the emergency surgical nature of the GDV. The main limitations of this study include the possibilities of type I and type II errors, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…As such, preoperative thoracic radiographs are recommended to identify evidence of aspiration pneumonia and guide antimicrobial therapy. 10 Of a population of 101 dogs with GDV, Green et al 10 documented that at presentation 27% were tachypneic (RR 434 breaths/min), 20% had increased respiratory effort, 2% had respiratory distress, and 14% had evidence of aspiration pneumonia on preoperative thoracic radiographs. The development of the acute respiratory distress syndrome has also been reported in dogs with GDV.…”
Section: Respiratory Dysfunctionmentioning
confidence: 98%
See 2 more Smart Citations
“…As such, preoperative thoracic radiographs are recommended to identify evidence of aspiration pneumonia and guide antimicrobial therapy. 10 Of a population of 101 dogs with GDV, Green et al 10 documented that at presentation 27% were tachypneic (RR 434 breaths/min), 20% had increased respiratory effort, 2% had respiratory distress, and 14% had evidence of aspiration pneumonia on preoperative thoracic radiographs. The development of the acute respiratory distress syndrome has also been reported in dogs with GDV.…”
Section: Respiratory Dysfunctionmentioning
confidence: 98%
“…One recent study documented that 58.5% of dogs (38/66) with GDV were hyperlactatemic at presentation, 20 whereas another reported that 30% of dogs (30/101) had an admitting lactate level 4 6 mmol/L. 10 …”
Section: Cardiogenic Shockmentioning
confidence: 98%
See 1 more Smart Citation
“…Presently, there are few highly powered, large‐scale studies in the veterinary literature on which to base recommendations for using [LAC] measurements in patient evaluation and management. In an effort to provide some general guidelines, a literature search of PubMed, Scopus, and CAB Abstracts performed for this review identified 35 clinical studies that investigated [LAC] as a prognostic indicator in dogs and cats . As in the human medical literature, there was marked heterogeneity in study sizes, study populations, mortality, and selected lactate cut‐off points making comparison across studies challenging.…”
Section: Lactate As a Prognostic Indicatormentioning
confidence: 99%
“…Notably, [LAC] was a significant predictor of mortality in the acute patient physiologic and laboratory evaluation (APPLE) scoring system, which is a rigorous, veterinary, disease severity scoring system . In the 12 clinical studies in which mortality was reported, dogs with [LAC] above study‐specific cut‐offs always had a higher mortality than dogs with [LAC] below the cut‐offs . Across those studies, the difference in mortality ranged from 5 to 99% (calculated median 29%).…”
Section: Dogsmentioning
confidence: 99%